Diagnosis of oesophageal mucormycosis managed with medical therapy alone. Issue 10 (22nd October 2020) - Ringer, Matthew; Pischel, Lauren; Azar, Marwan Mikheal
Abstract : Mucormycosis is an invasive mould that can cause aggressive infection, particularly in immunocompromised patients. Though oesophageal mucormycosis is relatively rare, it remains an elusive and devastating manifestation of this disease. The management is also challenging, due to surgical morbidity and contraindications such as thrombocytopenia in immunocompromised hosts. In this report, we present the case of a 60-year-old Lebanese man with newly diagnosed acute myeloid leukaemia who developed oesophageal mucormycosis after induction chemotherapy with idarubicin/cytarabine (7+3). The diagnosis was made when the patient developed febrile neutropenia and odynophagia. CT scan of the chest revealed a thickened oesophagus. Oesophagogastroduodenoscopy with biopsy, histopathology and PCR were performed, resulting in the diagnosis of Rhizopus microsporus . The patient was successfully treated with liposomal amphotericin B and salvage posaconazole therapy without surgical intervention. We reviewed the clinical characteristics of the six published oesophageal mucormycosis reports from the literature.